ANALYSIS OF THE EFFECT OF PARTICLE DIAMETER AND MOISTURE CONTENT IN GRANULAR COLUMN COLLAPSE EXPERIMENTS - Alfarizki, Nawaf
Granular material is a macroscopic material commonly found in everyday life. One experiment for observing large amounts of granular material is the granular column collapse experiment. This experiment involves observing the final angle, length, height, time, and speed of the final deposit of a column collapse. It also examines the effect of the water content added to the granular material. The influence of grain size is also observed in this experiment. The water content added to the granular material affects the final angle, length, and height of the final deposit. The granular material used is hole-less pearl grain, varied into four sizes: 4 mm, 6 mm, 8 mm, 10 mm. The results show that water content can increase the final deposit angle, shorten the length, and raise the height of the final deposit. Regarding the time of the landslide, there is a maximum point of water content where the water can cause the greatest jamming effect and then decreases afterwards.